Pendidikan Agama Kristen dan Perannya dalam Memfasilitas Kerjasama Antar Budaya di Indonesia (International Forum of Researchers and Lecturers, 2024)
This article discusses the important role of Christian religious education in facilitating intercultural cooperation in Indonesia, which is a country with a pluralistic society. Religious education not only serves to build individual morals and character, but also serves as a bridge to create understanding and tolerance between different groups. By prioritizing the values of peace and mutual respect, Christian religious education has the potential to reduce conflict and promote harmony in a diverse society. Therefore, education about pluralism and the rights of adherents of other religions in the religious education curriculum is very important, in order to strengthen social solidarity and intercultural cooperation.